A Disaggregated Disequilibrium Model of the Labour Market. - Andrews, M; Nickell, S (1986)
This paper analyzes a number of disequilibrium models of the labor market. The most general of these assumes that the aggregate market consists of a series of submarkets, none of which are in excess demand, with the remainder being in excess supply. Assuming demands and supplies have a common structure across markets, with a normal error, then it is possible to write aggregate employment as a nonlinear function of the common structure and the parameters of the error distribution. Estimates of this model and various restricted versions of it are presented, including the standard run condition model and the equilibrium model.